An experimental investigation of the performance and emissions characteristics of a direct injection compression ignition engine running with LPG. (1st January 2013) - De, B.; Panua, R.S.
Existing diesel engines are under stringent emission regulation particularly of smoke and particulate matter in their exhaust. The potential benefits of using liquefied petroleum gas (LPG) as an alternative fuel in diesel engines are both economical and environmental. In the present paper an experimental research was carried out on an I.C. engine laboratory single cylinder, four-stroke variable compression ratio, direct injection diesel engine converted to LPG-diesel dual fuel mode to analyse the performance and emission characteristics of pure diesel first and then LPG-diesel dual fuel mode. The measurements were recorded for the compression ratio of 16, 17 and 18 at LPG substitution rates of 10%, 15%, 20%, 25% and 30% and varying the load from idle to rated load of 5.2 kW. Comparative results are given at constant engine speed, variable compression ratio and various engine loads for diesel and different LPG substitution rates, revealing the effect of diesel and different LPG substitutions combustion on engine performance and exhaust emissions.